Difficulties in the Development of Oral Speech Skills in English Language Learning and Opportunities to Overcome Them (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the challenges faced by English language learners (ELLs) in developing oral speech skills. It identifies key areas of difficulty, including pronunciation, fluency, vocabulary, and grammar, and explores the underlying cognitive, psychological, and social factors contributing to these difficulties. The article then presents a range of pedagogical approaches and strategies that can help ELLs overcome these barriers and achieve fluency in spoken English. Finally, it emphasizes the importance of fostering a supportive and engaging learning environment to promote effective oral communication development.